NILAI MORAL DALAM NOVEL GITANJALI SEBUAH PERSEMBAHAN UNTUK MENEMUKAN HATI KARYA FEBRIALDI R - Dyah Catur Septiani; Ahmad Ripai; Muhajir Muhajir (CV. Denasya Smart Publisher, 2026)
This study aims to describe the intrinsic elements and moral values in the novel Gitanjali: A Tribute to Finding the Heart by Febrialdi R. This study uses a qualitative descriptive approach. The research data consists of narrative and dialogue quotations in the novel obtained through a literature study technique using reading and note-taking techniques. Data analysis was conducted using qualitative descriptive techniques with narrative presentation. The results showed that the intrinsic elements of the novel included themes, plot, characters and characterization, setting, point of view, and message, with a total of 58 data points. The main themes of the novel were related to the struggle of life, spiritual journey, and human values. There were 16 moral values found, covering the relationship between humans and God, the relationship between humans and themselves, and the relationship between humans and other humans in a social context. It can be concluded that the novel Gitanjali contains relevant moral values and has the potential to be used as character learning material